2022
DOI: 10.3390/su14042279
|View full text |Cite
|
Sign up to set email alerts
|

A Capacity Cost-Sharing Contract for a Two-Stage Supply Chain with a Risk-Averse Supplier under a Bargaining Power

Abstract: This study considers a two-stage supply chain (SC) consisting of a single supplier and a manufacturer. When the manufacturer introduces a new product to the market, both the manufacturer and supplier should install production capacity in advance. Since capacity building often takes a long time, the demand is uncertain at the time of capacity decision making. The supplier often makes a conservative decision on capacity building to avoid possible capital risks due to excess capacity, which leads to the so-called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…They investigated how bargaining power affects the efficiency of SC coordination mechanisms and found an inverse U-shape relationship between buyers' bargaining power and technology improvement investment. Koo [21] examined the effect of bargaining power in setting the contract parameters in a CCS contract in a supplier-manufacturer supply chain environment. The author showed that channel-coordinated CCS contracts are feasible only within a specific range of bargaining power when capacity investment is required for both the supplier and the manufacturer.…”
Section: Bargaining Power In Supply Contractsmentioning
confidence: 99%
See 3 more Smart Citations
“…They investigated how bargaining power affects the efficiency of SC coordination mechanisms and found an inverse U-shape relationship between buyers' bargaining power and technology improvement investment. Koo [21] examined the effect of bargaining power in setting the contract parameters in a CCS contract in a supplier-manufacturer supply chain environment. The author showed that channel-coordinated CCS contracts are feasible only within a specific range of bargaining power when capacity investment is required for both the supplier and the manufacturer.…”
Section: Bargaining Power In Supply Contractsmentioning
confidence: 99%
“…The author showed that channel-coordinated CCS contracts are feasible only within a specific range of bargaining power when capacity investment is required for both the supplier and the manufacturer. This study builds upon the existing research [21] to explore approaches for designing supply contracts under all possible bargaining power scenarios.…”
Section: Bargaining Power In Supply Contractsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many scholars have studied the coordination of dual-channel supply chain, which is the second stream related to dual-channel supply. Different types of contracts have been adopted by scholars, such as two-part tariff contract [22,34,[38][39][40], revenue-sharing contract [41][42][43][44], cost-sharing contract [45][46][47][48] and buyback contracts [49]. All these studies are based on symmetrical information in the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%